The Frequency of CYP2C19*2 Gene Polymorphisms in Burkina Faso Patients Treated with Clopidogrel - Kagambèga YD; Ouattara AK; Ouédraogo TWC; Traoré L; Yaméogo NV; Simpore J (The Application of Clinical Genetics)
Yves Donald Kagambèga,1,2,* Abdoul Karim Ouattara,1,2,* Teega-Wendé Clarisse Ouédraogo,2,3 Lassina Traoré,2,3 Nobila Valentin Yaméogo,4 Jacques Simpore1,2 1Biological Sciences, Université Norbert Zongo/ Centre Universitaire de Manga, Koudougou, Burkina Faso; 2Biochimie Microbiologie, Laboratoire de Biologie Moléculaire et de Génétique (LABIOGENE) - Université Joseph KI-ZERBO, Ouagadougou, Burkina Faso; 3Unité de Biologie Moléculaire, Centre de Recherche Biomoléculaire Pietro Annigoni (CERBA), Ouagadougou, Burkina Faso; 4Service de Cardiologie, Centre Hospitalier Universitaire Yalgado Ouédraogo, Ouagadougou, Burkina Faso*These authors contributed equally to this workCorrespondence: Abdoul Karim Ouattara, Université Norbert Zongo/ Centre Universitaire de Manga, BP 376, Koudougou, Burkina Faso, Email abdoul-karim.ouattara@unz.bfPurpose: The hepatic cytochrome P450 2C19 (CYP2C19) superfamily plays a crucial role in converting clopidogrel into its active form. Polymorphisms in CYP2C19 significantly contribute to the interindividual variability observed, often resulting in persistent thromboembolic complications. This study aimed to assess the frequency of the CYP2C19*2 (rs4244285, 681 G>A1) polymorphism among patients with cardiovascular diseases undergoing clopidogrel therapy.Patients and Methods: This cross-sectional study recruited a total of seventy-three (73) patients from the Cardiology Department of the Centre Hospitalier Universitaire Yalgado Ouédraogo (CHU-YO) between January and June 2023. DNA was extracted from blood samples for CYP2C19*2 genotyping using PCR-RFLP.Results: Genetic analysis revealed frequencies of 65.8% for the wild-type CYP2C19*1/*1, 28.8% for the heterozygous CYP2C19*1/*2, and 2.7% for the homozygous variant CYP2C19*2/*2. The distribution of the genotypic frequencies was consistent with Hardy-Weinberg equilibrium (p> 0.05). The overall frequency of the CYP2C19*2 allele in the study population was 16.4%, with 12.5% observed in females and 19.5% in males.Conclusion: This study provides valuable insights into the frequency of the CYP2C19*2 polymorphism among cardiovascular patients in Burkina Faso, contributing to the limited data available on CYP2C19 polymorphisms in sub-Saharan Africa. The presence of loss-of-function alleles suggests a potential risk for reduced drug efficacy in a subset of individuals. As one of the pioneering studies in the region, these findings emphasize the importance of further research to understand the clinical implications of CYP2C19 polymorphisms.Keywords: CYP2C19, polymorphism, PCR-RFLP, cardiovascular diseases, clopidogrel, Burkina Faso